Adverb of Manner and Its Translation Found in the Novel “The Wonderful Wizard of Oz” - Juliarta, I Made; Wirawan, I Gede Nika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research study aimed to analyze the form of adverb of manner and its translation analysis found in the data source. This research study used the theory proposed by Brown and Miller (1991) in analyzing the tree diagram of adverb of manner and the theory of translation shift that was proposed by Catford in analyzing the types of translation in translating from source language into target language. Library research was the method used in collecting the data of adverb of manner and its translation found in the data source. The method used in analyzing data of adverb of manner was qualitative method. The data of adverb of manner were taken from the novel entitled “The Wonderful Wizad of Oz” written by W.W Denslow. The researcher of this study found that there was one adverb of manner found in the initial position and five adverbs of manner that were placed in the final position. Adverb of manner found in the data source was an adjective followed by ly- suffix. They were adverb of manner that could be filled in the sentence structure in the form of adverb of manner. Adverbs of manner are integral to the narrative style of The Wonderful Wizard of Oz. Translating them effectively ensures the target audience experiences the same tone, atmosphere, and character portrayal as the original readers.